PENGARUH PENGGUNAAN STRATEGI INKUIRI BERBANTUAN MEDIA AUDIOVISUAL TERHADAP KETERAMPILAN MENULIS TEKS FABEL SISWA KELAS VII SMP NEGERI 7 PADANG - Azmi, Rahma Yatul; R.,, Syahrul (Universitas Negeri Padang, 2019)
ABSTRACT The purpose of this study is three. First, describe the writing skills of fable texts of grade 7 students at SMP Negeri 7 Padang before using inquiry strategies assisted by audiovisual media. Second, describing the skill of writing fable texts in grade VII students of SMP Negeri 7 Padang after using inquiry strategies assisted by audiovisual media. Third, describe the influence of the use of inquiry strategies assisted by audiovisual media on fable text writing skills of seventh grade students of Padang 7 Public Middle School. This type of research is quantitative research with experimental methods. The design of this study was one group pretest and posttest design. The population in this study were seventh grade students of Padang 7 Public Middle School who were enrolled in 2018/2019 school year as many as 251 people. The sample in this study were 31 students who were determined using purposive sampling technique. The variables of this study were fable text writing skills before and after using inquiry learning strategies assisted by audiovisual media in seventh grade students of SMP Negeri 7 Padang. The instrument of this study was performance tests, namely tests of writing fable texts before and after using inquiry learning strategies assisted by audiovisual media. The results of this study are three, namely as follows. First, writing fable text skills before using the incuri strategy assisted by audiovisual media in grade VII students of Padang Public Middle School 7 were in a sufficient qualification (C) with an average of 62.37. Second, fable text writing skills after using inquiry strategies assisted by audiovisual media in class VII Padang 7 SMP Negeri are in Good qualification (B) with an average of 81.45. Third, based on the t-test, the alternative hypothesis (H1) is received at a significant level of 95% and the degree of freedom (dk) = n-1 because of t count> t table, which is 6.17> 1.70. Kata Kunci: pengaruh, strategi inkuiri, keterampilan menulis teks fabel